Optimization of polymer blend electrolytes with tuneable conductivity potentials - Nurhaziqah, A.M.S.; Ahmad, M.K.; Faridah, A.B.; Saputri, D.G.; Ramli, S.A.; Mamat, M.H.; Shimomura, M. (Elsevier, 2023)
The potential of electrolytes’ performance in electrochemical devices is among the leading research. There are several ways to improve the conductivity of electrolytes, including the employment of additive materials and polymer blends. This research aims to improve the conductivity of a polymer blend with quasi solid state electrolyte. Poly-methyl methacrylate (PMMA) and poly-vinylidene fluoride (PVdF) possed great electrochemical stability and thermal stability. Hence, these materials were chosen as the target polymer for the synthesis of the polymer blend. The electrical impedance spectroscopy (EIS) analysis showed an optimum conductivity value of 3.44 × 10− 6 Scm− 1 with the ratio of PMMA: PVdF (70:30) at ambient temperature. The dependent temperature of PBE was also analyzed to prove that the conductivity increases with the increment of temperature and low activation energy (Ea). The thermogravimetric analysis (TGA) shows the stability of PBE up to 651 ◦C. Through this research, there are several different concentrations of PBE to investigate the stability of PBE with great value in the conductivity performance.